Loading of the Lokika Sanggraha traditional delication in the establishment of the Book of Law National Criminal Law - I Made Artana,; Made Warka,; Otto Yudianto, (Technium Social Sciences Journal, 2021)
This type of research uses normative legal research. This violation of Lokika Sanggraha in the field of decency hasn’t been regulated in the Criminal Code, so legal reform is needed. Criminal law reform has a very important meaning, namely from a political, sociological and practical point of view. According to the political aspect, the independent state of Indonesia should naturally have its own Criminal Code. This is seen as a symbol and is a pride of a country that has been free from the snares of political colonialism. According to the sociological aspect, the regulation in criminal law is a reflection of the political ideology of a nation where the law is developing and according to the practical aspect, referring to the official text in the KUHP which is now in effect in Dutch, of course this will have the potential to be misinterpreted. So from this point of view the current Criminal Code must be formed with the National Language, namely Indonesian. Lokika Sanggraha customary criminal offenses with decency offenses in national criminal law both in the Criminal Code and other positive laws, the fact is that there is no single article that regulates these customary criminal offenses in positive law in Indonesia or national criminal law.